2005
DOI: 10.1016/j.pain.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor antagonist treatment at the time of nerve injury prevents injury-induced changes in spinal NR1 and NR2B subunit expression and increases the sensitivity of residual pain behaviours to subsequently administered NMDA receptor antagonists

Abstract: Spinal NMDA receptors (NMDA R) are important in neuropathic sensitisation and acute administration of antagonists can provide temporary attenuation of sensitisation. If establishment of the chronic pain state could be prevented by brief administration of such agents at or around the time of nerve injury (pre-emptive analgesia) it might be possible to avoid many of the unacceptable side effects associated with repeated administration of these or other antagonists. Several reports describe aspects of effective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 48 publications
4
41
2
1
Order By: Relevance
“…In a rat neuropathic pain model of L5 spinal nerve transection, there was reduced expression of NR2A, 15 whereas in a model of partial chronic constriction injury to the sciatic nerve there was increased expression of NR2B (but not NR2A) and reduced NR1 in the superficial dorsal horn. 63 In animal neuropathic pain models, NMDA receptor channel blockers such as memantine, MK801, and ketamine attenuate thermal and mechanical hyperalgesia in rats. 64 In a mouse model, conditional deletion of the NR1 subunit in spinal cord resulted in reductions in NMDAmediated current and inflammatory pain, 65 but that study did not address neuropathic pain.…”
Section: Function In Chronic Painmentioning
confidence: 99%
“…In a rat neuropathic pain model of L5 spinal nerve transection, there was reduced expression of NR2A, 15 whereas in a model of partial chronic constriction injury to the sciatic nerve there was increased expression of NR2B (but not NR2A) and reduced NR1 in the superficial dorsal horn. 63 In animal neuropathic pain models, NMDA receptor channel blockers such as memantine, MK801, and ketamine attenuate thermal and mechanical hyperalgesia in rats. 64 In a mouse model, conditional deletion of the NR1 subunit in spinal cord resulted in reductions in NMDAmediated current and inflammatory pain, 65 but that study did not address neuropathic pain.…”
Section: Function In Chronic Painmentioning
confidence: 99%
“…Several behavioral studies have demonstrated that memantine attenuates allodynia and hyperalgesia postsciatic nerve injury and formalin injection (Carlton and Hargett 1995;Eisenberg et al 1995;Medvedev et al 2004;Wilson et al 2005). Memantine, noncompetitive NMDA receptor antagonist, is being used now to be a clinically promising drug for Alzheimer's disease in Europe and USA, because of its low neurotoxicity (Kato 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that intrathecal strychnineinduced dynamic allodynia was inhibited by intrathecal sarcosine (and also by ALX1393), supporting the ability of GlyT1 inhibitor to enhance glycinergic inhibition. However, the expression of GlyT1 is very high in the laminae I and II of the dorsal horn (33), an area where the expression of NMDA receptors is rich (41,42). Glycine acts as an essential co-agonist of glutamate at NMDA receptors (30), and its binding to the modulatory site of NMDA receptor is necessary for ion-channel opening (31).…”
Section: Discussionmentioning
confidence: 99%